The importance of DNA barcode reference libraries and selection primer pair in monitoring fish diversity using environmental DNA metabarcoding - DEWI IMELDA ROESMA; DJONG HON TJONG; SYAIFULLAH SYAIFULLAH; NOFRITA NOFRITA; MUHAMMAD NAZRI JANRA; FURQAN DWIKI LINTANG PRAWIRA; VIOLA MUTIARA SALIS; DYTA RABBANI AIDIL (Society for Indonesian Biodiversity, 2023)
Abstract. Roesma DI, Tjong DH, Syaifullah, Nofrita, Janra MN, Prawira FDL,Salis VM, Aidil DR. 2023.The importance of DNA barcode reference libraries and selection primer pair in monitoring fish diversity using environmental DNA metabarcoding. Biodiversitas 24: 2251-2260. Environmental DNA (eDNA) metabarcoding has become an alternative method used for biodiversity monitoring of an ecosystem. The eDNA metabarcoding has advantages compared to the conventional method because it is non-invasive, quick, and requires less cost. However, the effectiveness of the eDNA method is highly dependent on the coverage of the DNA barcode reference and primerpair. A study using the eDNA method was conducted for fish biodiversity monitoring in Singkarak Lake. Two-liter water samples were collected using sterile bottle samples at each sampling site (five sites). The universal primers (Fish FI and Fish R1) used for Next-generation sequencing (GRIDION, Nanopore, Oxford Technologies). The study detected 152 fish species using eDNA metabarcoding. Ten species out of the 30 originally reported in Singkarak Lake were detected using eDNA metabarcoding. The low percentage of fish detected is thought to be due to several factors; incomplete/unavailability of freshwater fish DNA barcodes in Indonesia registered in the database repository, inappropriate primer pair selection, low DNA quality, and the absence of target species DNA in collected water samples. The results demonstrated the significance of correctly registering DNA barcodes to the database and appropriate primer pair selection to identify eDNA metabarcoding. This study provides recommendations using eDNA metabarcoding for monitoring in future work.